Analisis Pengaruh Penghargaan (Reward) dan Lingkungan Kerja Terhadap Kinerja Karyawan UKM Kue Balok yang Ada di Kabupaten Bekasi - Luthfi Rizki Gifari; Aulia Fashanah Hadining; Fahriza Nurul Azizah (Peneliti.net, 2021)
This study aims to explain the effect of the work environment and rewards on employee performance at UKM Kue Balok in Bekasi Regency. This study targets all employees who work at UKM Kue Balok in Bekasi Regency, totaling 10 people. The data collected were analyzed using Descriptive Analysis of Respondents' Level of Achievement. The results showed that (1) the work environment affects performance, (2) rewards affect performance. (3) both have an effect on the performance of employees working at UKM Kue Balok in Bekasi Regency.